The Protection of Personal and Property Rights Act 1988 – Update and Reflections - Atkin, Bill (Victoria University of Wellington Law Review, 2013)
This article coincides with the 25th anniversary of the passage of the Protection of Personal and Property Rights Act 1988. The Act provides mechanisms for decision-making on behalf of people who lack capacity to make decisions for themselves. It is of increasing importance as the population ages. The article looks at the origins of the legislation and its contemporary focus. Recent case law is explored and some challenges for the future outlined. While the need for the Act remains, it may be timely for a fuller review to be undertaken.